Prevalence of keratoconus in an adolescent population - Jorge E. Valdez-García; Rubén Sepúlveda; Jessica J. Salazar-Martínez; Juan F. Lozano-Ramírez (Revista Mexicana de Oftalmología, 2014)
Introduction: Keratoconus is an idiopathic and progressive disease, where the cornea develops an irregular and conical shape, being the most common form of dystrophy or corneal ectasia, developing between the age of 12 and 20. In Mexico, the epidemiological information about the pathology is scarce. Purpose: To explore the epidemiology of keratoconus in Mexico among adolescents, and to compare the prevalence with international literature reports. This study identified associated pathologies and examined the management of patients. Methods: A retrospective study was conducted in an ophthalmology clinic; 500 charts were randomly selected from patients between 10 and 20 years of age in order to acquire information about the identification of the patient; the patient's gender, birthday, and age; three principal diagnoses at the first visit; as well as refraction and visual acuity in both eyes. After this, statistical analysis of the information was done. Results: The prevalence rate of keratoconus was 1.8%, affecting 66% of females and 33.3% of males. The mean age of presentation was 16.1 years. The most frequently associated refractive error was compound myopic astigmatism (44.4%); 88.8% presented with bilateralism. The majority of patients were being managed conservatively. Conclusion: Through this study, we found that our statistics matched those of internationally published reports concerning the early age of onset of the disease and its corresponding bilateralism. However, contrary to the international reports, it was evident that this condition was more prevalent among the females in our study sample, and no other associated pathologies were found.